Improvement of Teaching Effectiveness for Autism Children - Norsuhaily, Abu Bakar; Zuraina, Ali; Jumadil, Saputra; Zailani, Jusoh; Mohammad Shaban, Alsmadi; Mohd Hamidi, Solahudin (SRN Intellectual Resources, 2022)
Autism is a developmental disorder that affects communication and interaction ability negatively. There has been an increase in its prevalence in current statistics. Consequently, NASOM teachers have also increased the need to teach children with autism. The purpose of this study is to investigate how autism teachers in NASOM can improve their education strategies in terms of knowledge, formation, and competences. The study's location is in Malaysia. The research data were obtained by means of the questionnaire quantitatively. 55 teacher interviews who teach autistic children in NASOM received the questionnaires. Issues were divided into sections like knowledge and competence. They showed, however, an interest in taking advanced courses to increase their skills strategies for autistic children. There is thus a need to improve training of trainers (ToT) and the module by adding more autism components. NASOM teachers also had to be given access to autism training because autism learning has progressed, and several scientifically effective strategies are now available. Several proposals were proposed by the researchers to improve the studies, training, skills, and ToT course presences of autistic students. Analysis was again analysed using t-test, correlation and Regression using SPSS version 20 software for the raw data obtained. The results showed that with their presence at the ToT course there was a difference in knowledge, training, and competency. The ToT course has been found to be effective but still the strategies teaching autistic children need to improve since the results showed moderate and low.